Analysis of Earthquake Hazard-Prone Areas Using Peak Ground Acceleration (PGA) Values in Enggano Island, Bengkulu - Hangga Novian Adi Putra (BULETIN FISIKA, 2026)
Enggano Island is one of the oceanic islands located on the outermost edge of Bengkulu Province, which makes it highly vulnerable to tectonic earthquake hazards. This study aims to analyze the level of earthquake hazard vulnerability in the Enggano Island region of Bengkulu Province by utilizing Peak Ground Acceleration (PGA) values as the main indicator for assessing earthquake hazard potential. This study was conducted using 37 earthquake events data that occurred in the vicinity of Enggano Island within the time span from 1990 to 2025. The earthquake data used in this analysis focused on events with a magnitude of 4 Mw or higher and depth less than 50 km. Based on the disaster vulnerability analysis in the Enggano Island area, the regions with the highest earthquake hazard levels are Banjar Sari, Meok, Malakoni, and also a portion of Apoho, which have a PGA range of 106 gal to 114 gal and VI MMI scale. The moderate hazard levels are upper parts of Banjar Sari, Meok, Apoho, and Malakoni, as well as the southern portions of Kaana and Kahyapu, which have a PGA range of 94 gal to 104 gal and VI MMI scale. In contrast, the areas with lower hazard levels are found in the northern parts of Kaana and Kahyapu, where the PGA ranges from 78 to 92 gal and corresponds to intensity level V on the MMI scale. This study indicates that Enggano Island falls within a moderate earthquake hazard category.